Islamic Enterpreneurship Theology as an Accelerating of MSME Growth in the City of Surabaya - Fitryani, Fitryani; Maulana, Alfin (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Islamic theology offers a framework that combines economic and social aspects, encouraging more ethical and sustainable business practices. The formulation of this research problem: 1) How are the principles of Islamic theology applied in entrepreneurial practice by MSME actors in the city of Surabaya? 2) What are the obstacles and challenges faced by MSME actors in integrating the principles of Islamic theology in their entrepreneurial practices? This research uses a qualitative approach to explore the understanding of the application of Islamic theology and Islamic economic principles. The technique for determining informants uses purposive sampling, data collection is carried out through in-depth interviews and data analysis in this study using the data triangulation technique. The findings of this study can provide a strong basis for policymakers to formulate programs that support the development of MSMEs based on Islamic values. The results show that lack of understanding and awareness, difficulty balancing spiritual and material values, unsupportive regulations, limited resources and infrastructure, and lack of community support are some of the main obstacles that need to be overcome. This research explores the application of Islamic entrepreneurship theology as an accelerator for the growth of MSMEs in the city of Surabaya. Islamic theological principles such as monotheism, fairness, trust, courtesy, and social responsibility play an important role in shaping more ethical and sustainable business practices. The government needs to make fiscal incentive policies and ease of access to sharia financing.